Obraz kobiet w powieści Elfriede Jelinek Amatorki (Językowe, literackie i kulturowe refleksje na temat jedności w różnorodności, 2023)
The image of women in the works of Elfriede Jelinek plays a significant role. In the novel entitled "Women as Lovers" the function of the main characters, which society and themselves assigned to them, is visible. Noteworthy is the way they relate to their chosen ones and how they are treated by them – always of secondary importance. Men are the most important. Women's needs, their professional and family fulfillment are not taken into consideration. Their role is limited to serving men and meeting their expectations. Although some of Brigitte and Paula's priorities differ, their lives boil down to similar patterns and behaviors. Also, they, limited by society, believe that they do not deserve full happiness and do everything to make the "be’shert" happy with their actions. There are moments of happiness in their lives, but these are fragments of the whole nightmare in which they are stuck. In the article, it is important to indicate what is the reason for their behavior and how they explain their choices. We are unable to see joy, happiness or true love in the song. There is no room for feelings – there is only blind faith in false beliefs.